Biocrust carbon exchange varies with crust type and time on Chihuahuan Desert gypsum soils - Hoellrich, Mikaela R.; James, Darren K.; Bustos, David; Darrouzet-Nardi, Anthony; Santiago, Louis S.; Pietrasiak, Nicole (Frontiers in Microbiology, 2023)
In dryland systems, biological soil crusts (biocrusts) can occupy large areas of plant interspaces, where they fix carbon following rain. Although distinct biocrust types contain different dominant photoautotrophs, few studies to date have documented carbon exchange over time from various biocrust types. This is especially true for gypsum soils. Our objective was to assess the carbon exchange of biocrust types established at the world’s largest gypsum dune field at White Sands National Park. We sampled five different biocrust types from a sand sheet location in three different years and seasons (summer 2020, fall 2021, and winter 2022) for carbon exchange measurements in controlled lab conditions. Biocrusts were rehydrated to full saturation and light incubated for 30min, 2hr, 6hr, 12hr, 24hr, and 36hr. Samples were then subject to a twelve-point light regime with a LI-6400XT photosynthesis system to determine carbon exchange. Biocrust carbon exchange values differed by biocrust type, by incubation time since wetting, and by date of field sampling. Lichens and mosses had higher gross and net carbon fixation rates than dark and light cyanobacterial crusts. High respiration rates were found after 0.5 hr and 2 hr incubation times as communities recovered from desiccation, leveling off after 6 hr incubation. Net carbon fixation of all types increased with longer incubation time, primarily as a result of decreasing respiration, which suggests rapid recovery of biocrust photosynthesis across types. However, net carbon fixation rates varied from year to year, likely as a product of time since the last rain event and environmental conditions preceding collection, with moss crusts being most sensitive to environmental stress at our study sites. Given the complexity of patterns discovered in our study, it is especially important to consider a multitude of factors when comparing biocrust carbon exchange rates across studies. Understanding the dynamics of biocrust carbon fixation in distinct crust types will enable greater precision of carbon cycling models and impacts of global climate change on dryland carbon cycling and ecosystem functioning.